(untitled) (Acta Scientiarum. Agronomy, 2016)
The type of stem growth in soybean is a distinguishing feature of cultivars. The genes Dt1 and Dt2 affect the termination of the stem, and the types of growth are classified as determinate, semi-determinate and indeterminate. Phenotypic characterization of the type of growth is complex and is occasionally erroneously described. The objective of this study was to map and validate molecular markers to classify the type of soybean growth to facilitate the description of cultivars and genotypic selection. Two populations were used for mapping and validation of molecular markers F2:3: T 117 (semi-determinate growth type) x Igra RA 518 RR (indeterminate growth type) and CD 235RR (determinate growth type) x Igra RA 518 RR. The study demonstrates that the association of the molecular marker with the gene GmTFL1b was efficient in the classification of soybean growth types. The marker sat_064 is connected to the Dt2 gene, which is located in the Liaison Group G of the consensus map of soybeans with a recombination frequency of 19.4%. Molecular markers for Dt1 and Dt2 genes efficiently described the genotypes of soybean stem growth and selection.